Composite vignettes of challenges faced by Canadian collegiate student-athletes negotiating the demands of university life. (July 2021) - Crocker, Bradley; Chard, Sidonie; Duncan, Lindsay
Abstract: Background: Student-athletes must balance demanding athletic, academic, and social roles, producing distinct challenges compared to other student populations. Objective: The purpose of this study was to explore and represent through a creative medium the challenges faced by Canadian university student-athletes associated with managing the demands of their athletic, academic, and social roles. Method: Data were collected using semi-structured interviews with 20 collegiate student-athletes from Canadian institutions who reflected on adverse experiences in academic, athletic, and social domains. Data analysis consisted of inductive thematic analysis, and the creation of composite vignettes to represent findings. Composite vignettes are a form of non-fiction storytelling fusing together accounts of multiple participants into narratives depicting key findings. Results: Five composite vignettes were created to depict thoughts and experiences described by participants relating to challenges of being a student-athlete. Each vignette begins with third-person description of their immediate setting, followed by an internal monologue reflecting on their circumstances. Conclusion: Findings are presented as vignettes to appeal to a broad audience, and to facilitate readers drawing upon their own experiences to form personally-relevant conclusions. The authors' interpretations and perspectives on practical implications are also offered. Highlights: Composite vignettes were created from interview data to depict challenges student-athletes face in the Canadian context. Composite vignettes make findings accessible, and facilitate readers forming personally-relevant conclusions. Practical recommendations directed towards college sport counselors, coaches and administrators are included.